Response of pearlmillet (Pennisetum glaucum L.) hybrids to different doses of fertilizer on yield and economics under irrigated condition in Western Rajasthan - Sachin Saini; P.S. Chauhan; Varsha Jeetarwal (Annals of Agricultural Research, 2026)
A field experiment was conducted during Kharif, 2022 at the Instructional Farm, College of Agriculture, Swami Keshwanand Rajasthan Agricultural University, Bikaner to study the response of pearlmillet (Pennsisetum glaucum L.) hybrids to different doses of fertilizer under irrigated condition in western Rajasthan. The treatments comprising four fertility levels (control, 60:40:20, 80:50:30 and 100:60:40 N:P:K kg ha-1) in main plots and five hybrids (RHB-177, HHB-299, MPMH-17, 86M90 and KPH-6277) in sub plots making 20 treatment combinations was laid out in split plot design with three replications. The results showed that in fertility level of 80:50:30 N:P:K kg ha-1 significantly higher yield attributes, grain and stover yield as well as net return and B: C ratio over rest of the fertility levels but it was remained statistically at par with fertility level of 100:60:40 N:P:K kg ha-1 in this regard. Further data showed that highest fertilizer use efficiency of fertility level recorded with 80:50:30 N:P:K kg ha-1 followed with increased the fertility level decreased the fertilizer use efficiency. Among pearl millet hybrids KPH-6277 recorded significantly higher grain and stover yield, net returns and B:C ratio over rest of the hybrids but 86M90 hybrid was found significantly at par in this regard. Interaction effect of fertility levels and pearl millet hybrids also found significant on grain and stover yield, gross and net returns and B:C ratio which were significantly higher under application of 80:50:30 N:P:K kg ha-1 along with KPH-6277 hybrid as compared to all other treatment combinations and it was at par with 100:60:40 N:P:K kg ha-1 along with KPH-6277 hybrid. Based on a one-year finding, it is determined that under irrigated condition in western Rajasthan, pearl millet hybrid KPH-6277 when fertilized with 80:50:30 N:P:K kg ha-1 proved its advantage by registering a higher B:C ratio and yielding grain and stover at a level consistent with fertility level of 100:60:40 N:P:K kg ha-1.